A study of the association between peripheral arterial disease and diabetic foot ulcers - قدور إهاب; حسام كنجو; علي كفا (Latakia University Journal -Medical Sciences Series, 2022)
Background and aim of the study: The objective of the study is to determine the proportion of diabetic foot patients , which have an associated peripheral arterial disease. Methods: The study included diabetic patients admitted to the Vascular Surgery Division between 1-1-2021 and 31-12-2021 with foot ulcers. A comprehensive clinical examination was conducted for patients with an assessment of ulcers and their classification according to the Megitt-Wagner classification, in addition to investigating the presence of peripheral vascular disease using clinical examination, ankle-brachial index, Vascular doppler and the use of contrast imaging when a conclusive diagnosis was not reached using the previous investigations. Peripheral arterial disease was diagnosed if: nonpalpable peripheral pulse in one or more arteries, ABI <0.91, non triphasic arterial waveforms, and angiographic-documented peripheral arterial disease. Accordingly, the data was studied. Results: A total of 56 patients (38 males, 18 females, average age 58.23 ± 6.2 years) who fulfilled the inclusion criteria were enrolled in the study. The prevalence of peripheral vascular disease in the study sample was 30.4%. Lower values of the ankle-brachial index were observed in more severe grades of Wagner’s classification of ulcers. The duration of diabetes was longer in patients with peripheral arterial disease, with a mean of 14.82±3.1 years, and this relationship was statistically significant, p-value=0.001. Conclusion: The prevalence of peripheral arterial disease in patients with diabetic foot ulcers was 30.4%, and there was a significant relationship between the longer duration of diabetes and the presence of peripheral arterial disease.